Bedside Toxidromic Evaluation and Qualitative Analytical Screening in Acute Poisoning Cases Presenting to a Tertiary Care Emergency Department: An Observational Cross-Sectional Study - Richa Choudhary; Dr Pradeep Kumar Yadav; Vivek Pathak; Madhulika Shukla (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Acute poisoning still represents a major health emergency and an important public health issue, especially in low- and middle-income countries where pesticides, pharmaceuticals, alcohol, and everyday household toxins are widely available. Early bedside recognition of a toxidrome can guide immediate lifesaving treatment, while qualitative analytical screening testing may provide presumptive laboratory support to the clinical diagnosis. To identify common poisoning agents based on bedside toxidromic assessment and to correlate toxidromic diagnosis with qualitative analytical screening test findings. Methods: This prospective, hospital-based, observational, cross-sectional study was conducted in the Emergency Department and Department of Forensic Medicine and Toxicology of a tertiary care teaching hospital in North India. The study was conducted over a time period of 18 months from July 2024 to December 2025. Eighty-six adult patients with suspected acute poisoning were enrolled by consecutive sampling after obtaining informed consent from the patient or legally authorized representative. Demographic details, clinical features, toxidromic category, probable poison type, qualitative color-test findings, and immediate hospital outcome were recorded and analyzed using Statistical Package for the Social Sciences (SPSS) version 24.0. Results: The mean age of the patients was 32.90±11.31 years, and the commonest age group was 21-30 years (37.21%). Males constituted 67.44% of cases. Organophosphate (OP) poisoning was the most common type (41.86%), followed by drug overdose (23.26%), alcohol (13.95%), and other poisons (20.93%). Cholinergic toxidrome was the most common toxidrome (39.53%), followed by sedative (18.60%), sympathomimetic (16.28%), opioid (13.95%), and anticholinergic (11.63%). Toxidrome was significantly associated with outcome (p = 0.011), and the type of poison was also significantly associated with outcome (p = 0.018). Cholinergic toxidrome showed the highest qualitative test positivity, with 29 of 34 clinically suspected cases showing positive qualitative findings. Conclusion: Bedside toxidromic assessment is a useful early clinical tool in acute poisoning, particularly in suspected organophosphate poisoning. Qualitative analytical tests provide only presumptive laboratory support, but they should be interpreted along with clinical findings and not as a substitute for definitive instrumental confirmation.